2020
DOI: 10.1159/000508211
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Volume Index Predicts New-Onset Atrial Fibrillation and Stroke Recurrence in Patients with Embolic Stroke of Undetermined Source

Abstract: Introduction: It is unclear which surrogate of atrial cardiopathy best predicts the risk of developing a recurrent ischemic stroke in embolic stroke of undetermined source (ESUS). Left atrial diameter (LAD) and LAD index (LADi) are often used as markers of left atrial enlargement in current ESUS research, but left atrial volume index (LAVi) has been found to be a better predictor of cardiovascular outcomes in other patient populations. Objective: We aim to compare the performance of LAVi, LAD, and LADi in pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 20 publications
2
30
0
3
Order By: Relevance
“…We again confirmed our previous study [16] as well as others [7] that LA diameter is a predictor for AF detection in CS patients. Furthermore, the new data are consistent with previous literature that PR interval and LA volume index are also positive predictors for AF detection in this population [6,9,17]. However, in disagreement with a previous publication [9], we found LA diameter index is also a predictor for AF.…”
Section: Predictors For Af Detection In Cs Patientssupporting
confidence: 78%
See 2 more Smart Citations
“…We again confirmed our previous study [16] as well as others [7] that LA diameter is a predictor for AF detection in CS patients. Furthermore, the new data are consistent with previous literature that PR interval and LA volume index are also positive predictors for AF detection in this population [6,9,17]. However, in disagreement with a previous publication [9], we found LA diameter index is also a predictor for AF.…”
Section: Predictors For Af Detection In Cs Patientssupporting
confidence: 78%
“…Studies with prolonged cardiac monitoring, by either implantable cardiac monitor (ICM) or 30-day cardiac event monitor (CEM), have significantly increased the rate of AF detection in CS patients [4,5]. Several premorbid factors have been identified to predict AF detection, and associated with increased risk of ischemic stroke [6][7][8][9][10][11][12]. Many of these factors are biomarkers of atrial cardiopathy.…”
Section: Paroxysmal Atrial Fibrillation (Af) Has Been Recognizedmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our ESUS patients generally did not undergo more than 24 hr of heart rhythm monitoring, which may underestimate the incidence of AF, since continuous ECG monitoring for at least 72 hr with an increased proportion of AF detection was recommended for patients with ischemic stroke or TIA (Schnabel et al, 2019). Third, the left atrial diameter was used as a measure of sLAE, while investigations have shown left atrial volume index to be a better marker of atrial cardiopathy (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of left atrial (LA) dimensions as well as composite surrogate measures such as the LA volume index (LAVi) have been shown to demonstrate atrial cardiopathy and predict the development of new-onset AF and strokes [14-16]. Although an echocardiographic assessment is part of the work-up for ESUS, it may not always be available in clinical practice at the point of initial patient contact.…”
Section: Introductionmentioning
confidence: 99%